PROJECT-BASED DIGITAL GUIDEBOOK: LEARNING TO WRITE SPEECH TEXTS FOR ELEMENTARY STUDENTS - Ivanka, Afrilia Bayu; Pratiwi, Cerianing Putri; Listiani, Ivayuni (Universitas Labuhanbatu, 2025)
Purpose—This study aims to develop a project-based digital guidebook as teaching material for writing speech texts, specifically targeted at elementary school students.Methodology – This research follows the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) and involves exploratory research in 10 elementary schools. Data collection methods include observation, interviews with teachers and students, and questionnaires. Observations and interviews are used to assess the Book's condition and the users' needs, while questionnaires are employed to gather input and assessments from experts, teachers, and students. Data analysis techniques include qualitative data analysis, carried out interactively and continuously until the data becomes saturated. The steps in data analysis are (1) Data collection, (2) Data reduction, (3) Data presentation, and (4) Conclusion drawing/verification.Findings – The findings indicate a strong demand for a project-based digital guidebook, deemed suitable for enhancing writing skills among grade VI students. The study concludes that the developed digital guidebook not only meets the educational needs of students and teachers but also serves as a valuable resource for improving writing skills in elementary education. The implications of this research are significant for educators, as it provides a structured approach to teaching writing through digital means, ultimately benefiting students by enhancing their written communication abilities.Significance – This research is expected to inspire further developments in educational materials tailored to the needs of elementary school students, promoting effective learning strategies for writing.Keywords: Digital guidebook, Project, Writing speech text